Clinical presentation and angiographic findings of acute myocardial infarction in young adults in Jazan region - Kamel H. Haider; Sultan Abdulwadoud Alshoabi; Ibrahim A. Alharbi; Moawia Gameraddin; Osamah M. Abdulaal; Awadia Gareeballah; Walaa M. Alsharif; Fahad H. Alhazmi; Abdualziz A. Qurashi; Khalid M. Aloufi; Ahmed I. Sayed (BMC Cardiovascular Disorders, 2023)
Abstract Background There is a paucity of information about the clinical features and angiographic findings in young patients with acute myocardial infarction (MI), especially in the Arab Peninsula countries. Objective The aim of this study was to assess the proposed risk factors, clinical presentation, and angiographic findings of acute myocardial infarction in young adults. Methods This prospective study included young (range, 18 to 45 years) patients who presented with acute MI based on clinical evaluation, laboratory investigation, and electrocardiogram, and they underwent a coronary angiography procedure. Key findings Data of 109 patients with a diagnosis of acute MI were collected. Patients’ mean age was 39.98 ± 7.52 years (range, 31 to 45 years), and 92.7% (101) were male. Smoking was the highest risk factor in 67% of patients, obesity and overweight in 66%, sedentary lifestyle in 64%, dyslipidaemia in 33%, and hypertension in 28%. Smoking was the most common risk factor for acute MI in males (p = 0.009), whereas sedentary lifestyle was the most common risk factor in females (p = 0.028). Chest pain typical of acute MI was the most common presenting symptom in 96% of patients (p < 0.001). On admission, 96% of patients were conscious, and 95% were oriented. On angiography, the left anterior descending artery (LAD) was affected in 57%, the right coronary artery (RCA) was affected in 42%, and the left circumflex artery (LCX) was affected in 32% of patients. The LAD was severely affected in 44%, the RCA was severely affected in 25.7%, and the LCX was severely affected in 19.26% of patients (p < 0.001). Conclusion Smoking, obesity, sedentary lifestyle, dyslipidaemia, and hypertension were the most common risk factors for acute MI. Smoking was the most common risk factor in males and sedentary lifestyle in females. The LAD was the most commonly affected coronary artery, followed by the RCA and LCX arteries, with the same order for severity of stenosis.